2006
DOI: 10.1002/jso.20475
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the prognosis of patients with esophageal cancer undergoing salvage surgery after definitive chemoradiotherapy

Abstract: Salvage surgery is a highly invasive and morbid operation, which is performed on immunocompromised hosts. The indication must be carefully considered, with care taken to avoid non-curative surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 12 publications
(13 reference statements)
6
73
0
3
Order By: Relevance
“…Eleven studies were identified in the initial literature search to meet inclusion criteria ( Figure 1) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). After screening, one further publication (23), was excluded as this institution published their outcomes in a follow-up publication, which was included in the analysis (16).…”
Section: Study and Patient Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven studies were identified in the initial literature search to meet inclusion criteria ( Figure 1) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). After screening, one further publication (23), was excluded as this institution published their outcomes in a follow-up publication, which was included in the analysis (16).…”
Section: Study and Patient Demographicsmentioning
confidence: 99%
“…After screening, one further publication (23), was excluded as this institution published their outcomes in a follow-up publication, which was included in the analysis (16). Therefore, ten comparative studies were included in this pooled final analysis (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). In total 1,906 patients were included, 563 in the salvage group and 1,343 in the NCRS group.…”
Section: Study and Patient Demographicsmentioning
confidence: 99%
“…To solve these drawbacks, recent research has focused on the gene expression that can predict CRTx response (Eschrich et al, 2009;He et al, 2009;Maher et al, 2009). Second, multivariate analysis revealed that the most significant factor associated with longterm survival was a R0 resection (Chao et al, 2009;Tomimaru et al, 2006). No patients left with gross or microscopic residual tumors after salvage surgery (R1/R2 resections) survived more than 24 months in any series (Chao et al, 2009;Nakamura et al, 2004;Oki et al, 2007;Swisher et al, 2002;Tachimori et al, 2009;Tomimaru et al, 2006).…”
Section: Definitive Crtx For Resectable Ecmentioning
confidence: 96%
“…However, salvage surgery is a highly invasive and complex treatment leading to increased morbidity (50-79%) and in-hospital mortality (7-22%) as compared with those after neoadjuvant CRTx, due to the adverse events of predominantly respiratory complications and anastomotic leakage (Chao et al, 2009;Nakamura et al, 2004;M. Nishimura et al, 2007;Oki et al, 2007;Smithers et al, 2007;Swisher et al, 2002;Tachimori et al, 2009;Tomimaru et al, 2006). These hospital mortality rates are obviously higher than those for esophagectomy in Japan reported from specialized centers (2%) (Tachimori et al, 2009) or the nationwide registry (5%) (The Japan Esophageal Society).…”
Section: Definitive Crtx For Resectable Ecmentioning
confidence: 99%
See 1 more Smart Citation